The Legal Protection in The Use of Authentic Deeds in The Patent License Agreements - Mulyana, Silvia Sofiatunnisa; Fauza Mayana, Ranti; Gultom, Elisatris (Alauddin Law Development Journal, 2024)
This research examines the urgency of incorporating authentic deeds in patent licensing agreements and formulating such documents to establish legal safeguards that enhance the effectiveness of patent licensing ventures. This study employed a normative juridical approach with analytical descriptive methods. The results showed that the integration of authentic deeds in patent licensing agreements ensures legal certainty for the involved parties, as these deeds serve as conclusive evidence to validate legal actions taken by the parties. Furthermore, authentic deeds act as a deterrent against bad faith actions by preventing parties from disavowing the agreement’s contents. Additionally, there are no specific government-mandated formulations for patent licensing agreements. To achieve optimal legal protection, the formulation of an authentic deed in a patent license agreement should encompass aspects such as license exclusivity, limitations on patent usage, annual patent fees, information disclosure clauses, the equilibrium of patent use, sanctions, and dispute resolution.